Theories of nationalism : a critical introduction - Ozkirimli, Umut (Palgrave, 2017)
"This widely-used and highly-acclaimed text provides a comprehensive and balanced introduction to the main theoretical perspectives on nationalism. The 3rd edition has been revised and updated throughout and includes a new chapter on the practical outworking of theory in the contemporary politics of nationalism. The author situates the major theoretical approaches to nationalism within their historical context, alongside which he presents a unique critique of each theory, and shows how they can be applied to global events in the modern day. In doing so, the text exposes the limits of current discussions on nationalism, and issues a call for an expansion of the agenda of nationalism studies."--Provided by publisher.